Effect of Mixed Feed on Growth Performance in Fattening Cattle - YANG, Keopaserd; INTHAPANYA , Sangkhom; NAOYENG , Khamkeo (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This study undertook an assessment of different levels of mixed feed on growth performance in fattening cattle. This research was carried out at the Northern of Agriculture and Forestry College. The design was used Randomized Completely Block Design (RCBD) with 4 treatments and 4 replicates as: (1) MF-0= Ruzi grass only; (2) MF-1= Ruzi grass plus mixed feed at 1% of LW; (3) MF-2= Ruzi grass plus mixed feed at 2% of LW; and (4) MF-3= Ruzi grass plus mixed feed at 3% of LW. Each animal was weighted before and every 15days for evaluate the live weight change. Feed offer and residue were collected every day for calculate the feed intake and feed conversion ratio. The results showed that feed intake (Total DM intake) was significant (Prob<0.05) with 4 treatments in terms of added MF at 3% of LW and was increased feed intake by 32.4% when compared with MF-0. The ADG was significant (Prob<0.05) and was better live weight gain for MF-3 compared with MF-2 or MF-1 and MF-0 (The live weight gain was increased value for MF-3 by 51.3%). The feed conversion ratio (FCR) was better for MF-2, MF-1 or MF-0 replaced by MF-3 respectively. However, when increased the levels of mixed feed in the diets of 1; 2; and 3% of live weight were increased profited. The result concluded that fattening cattle using Ruzi grass as basal diet when supplement with MF feed at 3% of live weight was positive affected to feed intake; growth rate and profits better than levels of MF at 2 or 1 and 0% of LW.